Panorama of high mountain Inca sanctuaries in Argentina - Ceruti, María Constanza (2007)
The Inca occupation of the Southern Andes involved the physical access to summits over 5.000 meters above sea level for the purpose of sacrifices and offerings articulated within the frame of the capacocha ceremonies The survey of dozens of peaks in diverse orographic systems in the argentine territory from the volcanoes in the Puna highlands to the mountain ranges in the southernmost corner of the Inca empire conform a wide range of archaeological data which can be interpreted with the help of historical sources, as well as ethnographic and ethno-archaeological models. In this paper we approach the diversity of the mountaintop shrines surveyed and excavated by the author in Argentina, which is interpreted in relation to the social use, political purpose and symbolic meaning of the sacred geography in the strategies of legitimization of the Inca domination in the Andes.